From farm to fork – A life cycle assessment of fresh Austrian pork. (10th March 2016) - Winkler, Thomas; Schopf, Kerstin; Aschemann, Ralf; Winiwarter, Wilfried
Abstract: With 7.5% total nutritional value, pork is a staple food for many members of the Austrian population. Among members of the general public, little is known about the environmental impacts "from farm to fork" in the production of pork. This paper identifies three main impact categories for the environmental profile of Austrian pork using the Life Cycle Assessment (LCA) method. In a transparent and comprehensive manner, this LCA studied environmental impacts occurring throughout the production chain of pork, also including the transport and consumption stages. The results are expressed in terms of the global warming potential (GWP), soil acidification and eutrophication, specifically in CO2 -equivalents, SO2 -equivalents and NO3 -equivalents normalized to one kg of fresh Austrian pork (carcass weight) as the functional unit. The main results of the study indicated that the environmental burden is primarily related to the farming stage: 92.3% of GWP, 98.4% of soil acidification and 95.4% of eutrophication. The processes taking place after the agriculture stage (i.e., during the slaughtering stage, retail market and consumption) play a minor role, except for the relative impact of eutrophication during the slaughtering stage. The transportation that took place between the different life cycle stages only marginally influenced the emissions analysed, with private transport from the retail market to the household contributing most of the emissions considered in this part of the life cycle. These results point to the farming stage as the main focus for future improvements. Due to its high contribution to the GWP, soil acidification and eutrophication potential, enhancing the efficiency and environmental protection measures implemented during the farming stage (or improving the choice of commodities used from feed production) could generate the highest reductions in impacts on soil acidification, eutrophication and potentially on the global climate. Highlights: First comprehensive LCA of Austrian fresh pork. LCA incl. consumer phase, usually neglected by national LCAs of food products. Importance of nitrogen abatement for different impact categories. Detailed comparison of similar LCAs of pork.